2012
DOI: 10.1177/0022022112443854
|View full text |Cite
|
Sign up to set email alerts
|

Machismo and Marital Satisfaction in Mexican American Couples

Abstract: Traditional machismo in Mexican American culture has been considered detrimental to marital satisfaction (MS). Contrary to this notion, contemporary views of machismo suggest that masculinity in Mexican American couples is contextual and fluid along a continuum of positive and negative dimensions. In this study, the dyadic effects of positive and negative machismo on MS in Mexican American couples were explored using actor-partner interdependence model (APIM) analyses. A sample of 112 Mexican American couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
3
21
0
1
Order By: Relevance
“…The cultural value of caballerismo promotes the idea that men are expected to be well mannered, noble, sincere, and respectful toward women. In their study on Mexican American couples, Pardo et al (2013) found that dimensions of caballerismo (e.g., relationship accountability) were associated with higher relationship satisfaction (e.g., stronger emotional attachment to spouse). This may be because men who endorse caballerismo are more likely to be empathetic and compassionate toward their partners (Arciniega et al, 2008).…”
Section: Caballerismomentioning
confidence: 98%
See 2 more Smart Citations
“…The cultural value of caballerismo promotes the idea that men are expected to be well mannered, noble, sincere, and respectful toward women. In their study on Mexican American couples, Pardo et al (2013) found that dimensions of caballerismo (e.g., relationship accountability) were associated with higher relationship satisfaction (e.g., stronger emotional attachment to spouse). This may be because men who endorse caballerismo are more likely to be empathetic and compassionate toward their partners (Arciniega et al, 2008).…”
Section: Caballerismomentioning
confidence: 98%
“…While research has demonstrated that Latino adolescents endorse traditional values of machismo (Céspedes & Huey Jr., 2008); there is a dearth of literature exploring these values with Mexican samples in the context of their romantic relationships. One exception is Pardo, Weisfeld, Hill, and Slatcher (2013), who explored the effects of machismo on marital satisfaction in a sample of Mexican American couples (Mage = 37.30). They found that husbands who subscribed to more traditional views of machismo (e.g., dominance, aggressiveness) also reported poorer relationship satisfaction (e.g., lower emotional attachment to spouse).…”
Section: Machismomentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in marital satisfaction are usually explained by male dominance in marriage, characterised by unequal control of family finances, higher risk for interpersonal violence, and double standards in regard to sexual behaviour. Pardo, Weisfeld, Hill, and Slatcher (2013) found that gender differences in marital satisfaction differ across cultures due to traditional sex roles, while Taniguchi and Kaufman (2013) found that gender differences in marital satisfaction may be attributed to culture related variables, such as sex egalitarianism. Diener (2000, p. 34) argues that subjective well-being (SWB) refers to people's evaluations of their lives, both affective and cognitive.…”
Section: Gender Differences In Marital Satisfactionmentioning
confidence: 99%
“…Along with a strong promotion of masculinity and early sexual behavior, machismo also refers to displays of strength, aggression, and protective behaviors toward family (Pardo et al 2012). In the Latino culture, decisions regarding sexual intercourse and discussion of sexual topics are commonly the responsibility of the men and it is considered inappropriate for women to discuss sexuality (Rojas-Guyler, Ellis, and Sanders 2005).…”
Section: Traditional Gender Roles and Hiv Riskmentioning
confidence: 99%